Relationship Between Sensation Seeking and Risk-Taking Behavior on Mountain Climber - Frysta Dwi Permadani; Miftakhul Jannah (JUARA : Jurnal Olahraga, 2022)
The background of the research is the importance of risk-taking behaviour for climbers in making decisions before climbing, both physically and financially. This study aims to determine the relationship between sensation seeking and mountain climbers' risk-taking behaviour. This research uses quantitative research methods. The sampling technique used was the saturated sample technique. The total population and sample consisted of 80 Jejak Angin Alas community climbers. This research data collection using a questionnaire. The data analysis technique uses the product-moment correlation technique. The results of this study indicate that there is a significant relationship between sensation seeking and risk-taking behaviour in mountain climbers. In this case, it can be interpreted that the higher the sense of seeking possessed by mountain climbers, the higher the risk-taking behaviour they receive.